Effectiveness of Active and Cooperative Learning Technique Named Learning together for Technical Topic-A Case Study - Patil, Yogesh S. (Journal of Engineering Education Transformations, 2016)
The purpose of this study is to investigate the effects of cooperative learning methods and collaborative learning technique named learning together on final year B.Tech students of Automobile Engineering Department, RIT Sakhrale. This experiment is conducted for technical subject named "Engine Design" in seventh semester for topic Flywheel design. In this experimental study, students were divided into two groups named experimental group and a control group. There were 29 students in the control group and 35 students in the experimental group. Learning together cooperative learning technique is applied for experimental group to teach a topic named Flywheel design. A same topic is taught to control group by using traditional method of chalk and talk. A small test was conducted on same topic with design questions for both groups and results are analyzed. At the end of session experimental group students are asked to fill feedback form. Result of this research shows significant difference between the levels of achievements between the experimental group and traditional group.